Communicating the Neuroscience of Psychopathy and Its Influence on Moral Behavior: Protocol of Two Experimental Studies - Blakey, Robert; Askelund, Adrian D.; Boccanera, Matilde; Immonen, Johanna; Plohl, Nejc; Popham, Cassandra; Sorger, Clarissa; Stuhlreyer, Julia (Frontiers in Psychology, 2017)
Neuroscience has identified brain structures and functions that correlate with psychopathic tendencies. Since psychopathic traits can be traced back to physical neural attributes, it has been argued that psychopaths are not truly responsible for their actions and therefore should not be blamed for their psychopathic behaviors. This experimental research aims to evaluate what effect communicating this theory of psychopathy has on the moral behavior of lay people. If psychopathy is blamed on the brain, people may feel less morally responsible for their own psychopathic tendencies and therefore may be more likely to display those tendencies. An online study will provide participants with false feedback about their psychopathic traits supposedly based on their digital footprint (i.e., Facebook likes), thus classifying them as having either above-average or below-average psychopathic traits and describing psychopathy in cognitive or neurobiological terms. This particular study will assess the extent to which lay people are influenced by feedback regarding their psychopathic traits, and how this might affect their moral behavior in online tasks. Public recognition of these potential negative consequences of neuroscience communication will also be assessed. A field study using the lost letter technique will be conducted to examine lay people’s endorsement of neurobiological, as compared to cognitive, explanations of psychopathy. This field and online experimental research could inform the future communication of neuroscience to the public in a way that is sensitive to the potential negative consequences of communicating such science. In particular, this research may have implications for the future means by which neurobiological predictors of offending can be safely communicated to offenders.